Proceedings of the 46th ACM Technical Symposium on Computer Science Education 2015
DOI: 10.1145/2676723.2677256
|View full text |Cite
|
Sign up to set email alerts
|

Scratch

Abstract: There is concern amongst teachers about how to support all pupils in making the transition from popular graphical languages like Scratch to text-based languages like Python. In a new subject, not taught widely before at both primary and secondary education in England, there is inevitably a lack of tuned-in pedagogical expertise. In this paper, the authors address the transition process by exploring established pedagogy in Computer Science, and other subjects including Mathematics, Science and Languages, and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…In a study by Romero and Dupont (2016), it was stated that through the use of educational robot kits in education, students’ skills in critical thinking, collaboration, creativity, problem solving, and computational thinking improved. The results of the current study are also consistent with statements published in research by Dorling and White (2015) and Park and Yoo (2018), in that primary and secondary school students are able to successfully learn text-based programming concepts and demonstrate effective performance. On the other hand, Keith et al (2019) observed that students’ computational thinking skills developed as a result of working with robotic activities, and saw robotic activities as an important tool in the development of learners’ computational thinking skills.…”
Section: Discussionsupporting
confidence: 89%
“…In a study by Romero and Dupont (2016), it was stated that through the use of educational robot kits in education, students’ skills in critical thinking, collaboration, creativity, problem solving, and computational thinking improved. The results of the current study are also consistent with statements published in research by Dorling and White (2015) and Park and Yoo (2018), in that primary and secondary school students are able to successfully learn text-based programming concepts and demonstrate effective performance. On the other hand, Keith et al (2019) observed that students’ computational thinking skills developed as a result of working with robotic activities, and saw robotic activities as an important tool in the development of learners’ computational thinking skills.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, research suggests that students working with block-based interfaces demonstrated greater interest and learning gains in future programming efforts [21], [22]. DSAScratch extends the possibilities offered by Scratch as an introductory programming tool to enable students to experiment with advanced algorithms before moving into Python or other more advanced programming languages [23]. Studies demonstrate that block-based approaches provide a greater advantage than text-based approaches in this context when introducing difficult concepts to novices [20], [24].…”
Section: Introductionmentioning
confidence: 96%
“…The constructionist programming approach in block-based environments like Scratch can result in poor programming practices because proper software engineering principles are not introduced (Dorling & White, 2015). Code smells are a useful method for identifying these bad practices.…”
Section: Introductionmentioning
confidence: 99%